PELAYANAN KARTU TANDA PENDUDUK DI KECAMATAN KABUPATEN SRAGEN - Yunisih, Arum - (JI@P, 2014)
Objective of this research is to know the problems relating to service ofResidence Identity Card in Sragen Sub Districk, Sragen Regency. One of themain task and function of Sub District Government level is to give service in fieldof residential affairs in general and in the field of Residence Identity Cardproduction in particular. In fact, however, people often complain due to thediscrimination by the Sub District official, unclear tariff, too bureaucratic, and lackof access to information. Such kind of service opens the opportunity of whatsocalled âred tapeâ. Relating to that fact, this research is interested in studyingservice given by the officials of Sub District level in the production of ResidenceIdentity Card. Imbedded case study method was used in this study.Respondents of this study were the government officials who are in charge toserve to produce Residence Identity Card, community member who appeal tohave Recidence Identity Card, and the brokers. They were selected as therespondents on the basis of purposive sampling. This research usedobservation, interview, and documentation study as the method of collectingdata. Interactive model analysis was used. To validate the data, triangulationdata and method were used. Research result shows that production ofResidence Identity Card has already worked effectively. It is shown by the factthat the production of Residence Identity Card conforms with need and desire ofthe service users. This proved by the fast and accurate service, and by theproffessional officias in charge. Some related probles of service appear,however, tecchnical and administrative problems such as turning off electricitypower, unreadiness of stock of form, limited computer, lack of administrativepersonnel obstruct service process. In general, service on production ofRecidence Identity Card is influenced by either internal or external factors.Internal factors include low reward or material incentive for the civil servants whoare in charge. External factors include the interest of service users and thenetwork of the brokers.Key words: Residence Identity Card, service, user, broker.